Hygrothermal Behavior, Building Pathology and Durability - de Freitas, Vasco Peixoto de.; Delgado, J.M.P.Q.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The main purpose of this book, Hygrothermal, Building Pathology and Durability, is to provide a collection of recent research works to contribute to the systematization and dissemination of knowledge related to construction pathology, hygrothermal behaviour of buildings, durability and diagnostic techniques and, simultaneously, to show the most recent advances in this domain. It includes a set of new developments in the field of building physics and hygrothermal behaviour, durability approach for historical and old buildings and building pathology vs. durability. The book is divided in several chapters that are a resume of the current state of knowledge for benefit of professional colleagues, scientists, students, practitioners, lecturers and other interested parties to network.
Reducing the Risk of Microbial Growth on Insulated Walls by Improving the Properties of the Surface Materials -- Biological Defacement of External Thermal Insulation Composite Systems (ETICS) -- Effectiveness and Durability of Biocides in Building Coatings – Biological Aspects -- Hygrothermal Conditions and Mould Growth Potential in Cold Attics – Impact of Weather, Building System and Construction Design Characteristics -- Controlled Ventilation of Historic Buildings – Assessment of Impact on the Indoor Environment via Hygrothermal Building Simulation -- Degradation Control of Historical Walls with Rising Damp Problems -- Hygrothermal Performance and Damage Risk of Green Roofs -- Applicability of the Pull-Off Test: Teachings from a Large Sample of In-Situ Tests -- Moisture Robustness during Retrofitting of Timber Frame Walls with Vacuum Insulation Panels – Experimental and Theoretical Studies -- Wind Resistance Evaluation to Dynamic Response of Mechanically Anchored Waterproofing Membrane System.-.
Keywords: Building materials; Building construction; Structural materials; Building Materials; Building Physics, HVAC; Structural Materials